Affinity chromatography studies for mespilus germanica L. polyphenol oxidase - Cavdar, Aysin; Karakus, Emine; Bilen, Cigdem (SPRINGER, 2025)
Polyphenol oxidase (PPO) enzymes perform enzymatic browning reactions by hydroxylation of monophenols to o-diphenols and oxidation of o-diphenols to o-quinones called phenolic substances in foods. Medlar fruit (Mespilus germanica L.) was used as an enzyme source which is a rich antioxidant and antiviral properties as well as its commercial value in food industry. PPO enzyme was partially purified using the homogenization step and ammonium sulfate precipitation 0-80%, respectively. Characterization studies were applied to determine the optimum substrate, buffer concentration, pH, and temperature for catechol as 0.1 M, pH: 6.8, and 15 & ring;C, respectively. Vmax and KM values of medlar PPO for catechol were calculated as 12,542.46 IU and 2.5 mM, respectively. Following, PPO enzyme was purified by Sepharose 4B-L-tyrosine-p-aminobenzoic acid (S-4B-TABA) and Sepharose 6B-L-tyrosine-p-aminobenzoic acid (S-6B-TABA) affinity gels. Purification degrees were achieved as 54.0 and 4.8 for S-4B-TABA and S-6B-TABA, respectively. The medlar PPOs purified by S-4B-TABA and S-6B-TABA affinity gels exhibited a single band at a level of 40 kDa in Native PAGE and SDS-PAGE that the enzyme was concluded to have only one single subunit. Medlar PPO was firstly achieved to be purified by affinity chromatography in this study. No any study about purification of medlar PPO by affinity chromatography has been found in literature yet.
Keywords: Polyphenol oxidase; Medlar; Mespilus germanica L; Affinity chromatography; Characterization; Kinetic constant; INHIBITION; PURIFICATION; FRUITS; PPO; MONOPHENOLASE; SUBSTRATE; ACID; Biotechnology & Applied Microbiology